Thrombotic Microangiopathy Secondary to COVID-19 in a Recent ABO-Incompatible Kidney Transplant - Castaneda, Zaira; Sellares, Joana; Torres, Irina B; Perello, Manel; Meneghini, Maria; Cidraque, Ignacio; Marquez-Algaba, Ester; Len, Oscar; Pons, Veronica; Parra, Rafael; Esperalba, Juliana; Donadeu, Laura; et al. (Archives of Clinical and Medical Case Reports, 2022)
De novo Thrombotic Microangiopathy (TMA) after renal transplantation is an uncommon complication which has been related with viral infections like the coronavirus disease (COVID-19). Severely immunosuppressed patients who acquire COVID-19 are at high risk of serious complications that should be carefully managed. We report a case of biopsy-proven TMA secondary to COVID-19 associated with Acute Respiratory Distress Syndrome (ARDS) in a recent ABO-incompatible kidney transplant. Eculizumab was initiated; and after 4 weekly doses, she recovered her renal function. Two months later, she was readmitted due to suspected organizing pneumonia, and received treatment with steroids. During the second week of admission, ARDS and TMA with neurological involvement were observed. Positive tests in blood and broncho-alveolar lavage for SARS-CoV-2 were obtained. A new cycle of eculizumab was started and convalescent plasma was associated due to persistent infection. The patient experienced progressive clinical improvement with resolution of respiratory function, neurological symptoms and hemolysis. Our case confirms that TMA could be triggered by COVID-19 and eculizumab is useful to control hemolysis and attenuate organ damage. Convalescent plasma should be considered in immune deficient high-risk patients with COVID-19.